Implementation of Asset Management Policy for the Parliament Office Area in Donggala Regency - Imam Hanafi; Ade Irma (Journal of Public Administration and Government, 2023)
This study aims to determine the Implementation of Regional Asset Management Policies at the Office of the House of Representatives of Donggala Regency. The type of research used in this research is qualitative research, with information selection techniques carried out deliberately. Data collection methods through observation, interviews, and documentation. Data analysis methods through data reduction, data presentation, data verification or conclusion drawing. This study uses Edward III Theory. The results of the research on the Implementation of the Regional Asset Management Policy of the Donggala Regency Regional House of Representatives Office are considered quite good. The implementation of the asset management policy of the Donggala Regency Regional People's Representative Council in terms of organizational structure has gone well. This is evidenced by the implementation of policies that are consistent with existing Standard Operating Procedures or performance standards. Inventory is also carried out by collecting data and labeling. In terms of resources, policy implementation is said to be lacking. This is indicated by the lack of human resources, both quantity and skills or competencies possessed by employees. In addition, financial resources or budgets are considered quite good. This is evident through the good response from the implementing agency and the consistent implementation of the policy. In terms of disposition, the implementation of the policy has been assessed quite well, this is shown by the good response of the implementers and their consistency in implementing the policy. In terms of communication, implementation of asset management guidelines at the Donggala RPRC Office is considered quite good. Bosses and staff always coordinate. Good communication makes the implementation to be carried out clearly because the transmission factor in receiving communication can be carried out properly.